Cloud-Based Online Tutoring Information System (BIMBELOL) - I Gede Sumiarta Adinata; I Made Sukarsa; Dwi Putra Githa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2021)
Tutoring is a guidance activity in terms of finding appropriate learning methods and overcoming learning difficulties. Generally, every tutoring process is carried out at the tutoring place. The general tutoring process can have a less effective and efficient impact during extreme weather and pandemics. Extreme weather and pandemic have resulted in delays to the end of the tutoring process. Problems that arise can be overcome by designing a system that can make the tutoring process more efficient and effective during extreme weather and pandemics. A cloud-based online tutoring information system (BIMBELOL) is a system that can help any tutoring process to be more efficient and effective. The use of cloud technology in making the system can help every tutoring process be carried out online. Testing of 40 respondents and black-box testing carried out on the system shows that each tutoring process has been successfully implemented.